Characterization of fowl aviadenovirus species in backyard flocks in Turkey - Kalin, R; Turan, T; Atasoy, M Ozan; Isidan, H (Journal of the Hellenic Veterinary Medical Society, 2022)
Fowl aviadenovirus infections show a worldwide distribution in poultry at all ages and the incidence of the disease is increasing year after year. Most of the studies have been exhibited the situation of the disease in commercial chickens especially in broilers but there is not sufficient data to estimate in backyards. Totally 389 internal organ samples were collected from 56 flocks from suspicious backyard chickens at ages between 10-35 weeks. Samples were tested by PCR method and nucleotide sequences of hexon genes were used for phylogenetic analyses and comparing with other FAdV sequences submitted to GenBank. Of the 389 samples, 23.9% were found FAdV positive and 30.4% (17/56) of the ﬂocks sampled in the study were infected. This is the first study that was carried out in backyards and two species (D and C) and four serotypes (FAdV-8a, FAdV-3, FAdV-4, and FAdV-10) have been discovered for the first time in Turkey. To understand the epidemiology of FAdV in Turkey and to get enough information about species and serotypes further large scale national studies should be carried out to determine the severity of FAdV infections and to plan control strategies.